2D nanosheet-assembled PdZnO microflowers for acetone sensor with enhanced performances. (January 2019) - Zhang, Yong-Hui; Cai, Xiao-Li; Song, Lian-Zhi; Feng, Fu-Yong; Ding, Jun-Yi; Gong, Fei-Long
Abstract: Hierarchical microflowers architecture assembled with 2D porous ZnO nanosheets were fabricated by a one-step solvothermal method and subsequent annealing process. A series of PdZnO have been produced by injecting various volumes of Pd(NO3 )2 ·2H2 O solution. The ZnO and PdZnO microflowers are applied to fabricate gas sensors to investigate their sensing characteristics for various gases at different operating temperatures. The 0.05 wt% PdZnO exhibit the highest selective enhancement of acetone (165%) than ammonia (0.9%), methanal (38%), methanol (71%), H2 (35%) and CO (15%). In addition, it possesses the lower operating temperature and shorter response/recovery times (11s, 5s) toward acetone gas compared with the pure ZnO microflowers. Graphical abstract: Highlights: 2D porous nanosheet-assembled ZnO microflowers were prepared. PdZnO was obtained by injecting Pd 2+ solution onto the surface of thin film. The Pd-doped ZnO sensors show enhanced performance for acetone vapor.